The impact of early sports participation on body fatness in adulthood is not mediated by current physical activity - Avelar, Ademar [UNESP]; Araujo, Monique Yndawe Castanho [UNESP]; da Silva, Camila Buonani [UNESP]; de Lima, Manoel Carlos Spiguel [UNESP]; Codogno, Jamile Sanches [UNESP]; Turi-Lynch, Bruna Camilo; Fernandes, Rômulo Araújo [UNESP]; Mantovani, Alessandra Madia [UNESP] (Wiley, 2024)
Objective: The aim was to analyze the relationship between early sports participation (ESP) and body fatness (BF) in adults, as well as to identify whether this possible relationship is directly influenced by the current physical activity (PA) level. Methods: This cross-sectional study combined baseline data of two cohort. The BF estimated by DXA. The ESP, the subjects reported the engagement in sports during childhood (7–10 years) and adolescence (11–17 years) through two yes/no questions and current PA (described as steps) was device—measured using pedometers. Were identified as potential covariates and therefore adjusted the multivariate models: age, ethnicity, alcohol consumption, smoking, and sleep quality. Statistical analysis consisted of the chi-square test, analysis of variance/covariance, and structural equation modeling (software BioEstat version 5.0; p-value <.05). Results: Adults engaged in ESP had lower BF; among women, the variance in BF explained by ESP was 25.5%; among men, it was 9.2%. Sports participation in early life (r = −.436 [95% CI: −0.527 to −0.346]) and current PA (r = −.431 [95% CI: −0.522 to −0.340]) were inversely related to BF, as well as positively related to each other (r =.328 [95% CI: 0.226 to 0.430]). In the mediation model, current PA partially mediated (18.5%) the impact of ESP on BF, while current PA and ESP remained relevant determinants of BF. Conclusion: Early sports participation and current PA have a significant impact on BF in adulthood, which is of similar magnitude and independent of each other.